Mercury and lead exposure in avian scavengers from the Pacific Northwest suggest risks to California condors: Implications for reintroduction and recovery. (December 2018) - Herring, Garth; Eagles-Smith, Collin A.; Varland, Daniel E.
Abstract: Mercury (Hg) and lead (Pb) are widespread contaminants that pose risks to avian scavengers. In fact, Pb exposure is the primary factor limiting population recovery in the endangered California condor ( Gymnogyps californianus ) and Hg can impair avian reproduction at environmentally relevant exposures. The Pacific Northwest region of the US was historically part of the condor's native range, and efforts are underway to expand recovery into this area. To identify potential threats to reintroduced condors we assessed foraging habitats, Hg and Pb exposure, and physiological responses in two surrogate avian scavenger species (common ravens [ Corvus corax ] and turkey vultures [ Cathartes aura ] across the region between 2012 and 2016. Mercury exposure near the Pacific coast was 17–27-fold higher than in inland areas, and stable carbon and sulfur isotopes ratios indicated that coastal scavengers were highly reliant on marine prey. In contrast, Pb concentrations were uniformly elevated across the region, with 18% of the birds exposed to subclinical poisoning levels. Elevated Pb concentrations were associated with lower delta-aminolevulinic acid dehydratase ( δ -ALAD) activity, and in ravens there was an interactive effect between Hg and Pb on fecal corticosterone concentrations. This interaction indicated that the effects of Hg and Pb exposure on the stress axis are bidirectional, and depend on the magnitude of simultaneous exposure to the other contaminant. Our results suggest that condors released to the Pacific Northwest may be exposed to both elevated Hg and Pb, posing challenges to management of future condor populations in the Pacific Northwest. Developing a robust monitoring program for reintroduced condors and surrogate scavengers will help both better understand the drivers of exposure and predict the likelihood of impaired health. These findings provide a strong foundation for such an effort, providing resource managers with valuable information to help mitigate potential risks. Graphical abstract: Image 1 Highlights: Mercury and lead were elevated in surrogate avian scavenger species in regions where California condors may soon be released. Coastal regions may expose condors to elevated mercury and lead, whereas interior regions may result in elevated lead. Interactive effects of mercury and lead influenced corticosterone concentrations both positively and negatively.